La région frontalière du Sud-Liban et les réfugiés palestiniens : entre résistance et contournements - Daniel Meier (L'Espace Politique)
The Palestinian question in Lebanon is usually studied through their political or economical conditions, mainly referring to their life in camps. This approach sometimes minimizes the importance of the 60-year old length common history of the Palestinian refugees with Lebanon and more particularly their relationship with this state’s geography. This article intends to make the link between those refugees and south Lebanon’s borderland. This border region opens a window on a long, painful and sometimes violent relationship with the land Palestine and with Israel as well as it raises questions about the possibilities of crossing between the two countries. Following two empirical axis with the armed resistance of the Palestinian resistance in the early seventies and the civilian resistance that intends to follow up relationships with relatives in Palestine, this paper would like to consider the region as a borderland and therefore explore the pertinence of using the concept of networked border to describe the type of issue faced by the Palestinians of Lebanon when reaching their relatives of Palestine. We will see that this civil and military aspect of the relationship with the border describes quite well the Palestinian refugees’ relationship with the borderland and its transformation in time. It also highlights the persistence of the marginalization of the Palestinian refugees through the issue of mobility as they try to cross or bypass the South Lebanese border and confronted with a networked or stratified system of borders.